Karakterisasi dan Suplementasi Nanofiber PVA-kurkumin pada Performa Pertumbuhan Ayam Broiler Minggu Pertama - Wirahadikesuma, Ikhwan; Manalu, Wasmen; Maheswari, Hera; Maddu, Akhiruddin; Almiahsari, Ashri; Rizki, Muhammad; Mia Fitriana, And; Wirahadikesuma, Ikhwan Wirahadikesuma (IPB University, 2025)
Broiler chickens are a vital global commodity, known for their rapid growth and efficiency, but their productivity has historically relied on Antibiotic Growth Promoters (AGP), necessitating the development of safe alternatives. This study aimed to assess the efficacy of Polyvinyl Alcohol (PVA)-curcumin nanofibers as a potential substitute for Antibiotic Growth Promoters (AGP) in improving the growth performance of broiler chickens. The nanofibers were synthesized via the electrospinning technique at varying PVA concentrations of 5%, 10%, and 15%, and their morphology was characterized by Scanning Electron Microscopy (SEM). The in vitro assay evaluated curcumin release profiles were measured in phosphate buffer (PBS, pH 7,4) at 37 °C. A seven-day in vivo experiment involving 30 broiler hens categorized into 5 groups to assess the impact of supplementation on body weight, feed intake, and feed conversion ratio (FCR). The synthesized PVA- curcumin nanofibers exhibited optimal dimensions (100–135 nm), with gradual curcumin release measuered at 43,5–51,5% at 5 minutes and 49,27–64,5% at 120 minutes. While statistical analysis showed no significant difference (p> 0,05). The treatment group showed higher average daily gain (ADG) (99,49–115,4 g) and feed intake (FI) (118,76–129,11 g), resulting in better feed conversion ratio (FCR) (0,921–1,00) compared to the control group. In conclusion, PVA-curcumin nanofibers were successfully synthesized, demonstrating their potential to improve growth performance, and are suitable as an alternative non-antibiotic growth promoter in broilers.